Drowning among the lakeside fishing communities in Uganda: results of a community survey - Kobusingye, Olive; Tumwesigye, Nazarius Mbona; Magoola, Joseph; Atuyambe, Lynn; Alonge, Olakunle (International journal of injury control and safety promotion, 2017)
The study aimed to determine the drowning burden in four Ugandan lakeside districts; the prevalence of life jacket use, and community knowledge and attitudes regarding water safety. Subjects were recruited as they disembarked from boats. A structured questionnaire was used for demographics, experience on water, details of incidents in water, and awareness of drowning prevention measures. Focus group discussions (FGDs) and key informant interviews were held. The study interviewed 544 participants; 81.1% male, 86.8% below 45 years, and 51.1% involved in the fishing industry. A quarter (26.1%) of the respondents were observed wearing life jackets as they disembarked. Participants who had been in a boat that nearly capsized (57.8%), or that actually capsized (21.7%), were no more likely to wear life jackets than those who had not had these experiences. Three quarters (73.2%) did not know how to call for rescue, and only 48.7% could swim. There drowning fatality rate in this community was 502 deaths per 100,000 population. Majority of drowning events occurred during transportation (51.7%) or fishing (39.0%). The most frequently mentioned factors were stormy weather and overloading. Drowning is a common threat to young adults in the fishing communities around Lake Victoria. Few preventive interventions are in place.